SPE Annual Technical Conference and Exhibition 2009
DOI: 10.2118/124918-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Compositional Modeling of CO2 Injection in Fractured Media Compared to Experimental Data

Abstract: In a recent PhD dissertation (Darvish 2007), data and modeling are presented from an experiment in which CO2 is injected in a tall vertical core, surrounded by fractures. After injecting CO2 for 22 days, 65% of the oil in place is recovered (and still increasing). However, the modeling with a commercial simulator results in only 12% recovery, despite adjusting parameters. We will discuss inherent flaws in current simulators that impede realistic simulation of CO2 injection in fractured media, even at laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…A denser phase above a less dense phase initiates convective currents that enhance the dissolution rate, thus accelerating dissolution of CO 2 in the aqueous phase. The initial stage of natural convection in a saturated porous layer with a denser fluid on top of a lighter fluid has been extensively studied by means of a linear stability analysis, numerical simulations and the energy method ( (Bachu et al, 1994;Class et al, 2009;Dentz and Tartakovsky, 2009;Elder, 1968;Ennis-King et al, 2005;Foster, 1965;Gasda, 2010;Khosrokhavar et al, 2014c;Meulenbroek et al, 2013;Moortgat et al, 2009;Myint and Firoozabadi, 2013;Nordbotten and Celia, 2011;Nordbotten et al, 2005;Pruess et al, 2003;Ranganathan et al, 2012;Riaz et al, 2006;Van Duijn et al, 2004;Walker and Homsy, 1978)). …”
Section: Introductionmentioning
confidence: 99%
“…A denser phase above a less dense phase initiates convective currents that enhance the dissolution rate, thus accelerating dissolution of CO 2 in the aqueous phase. The initial stage of natural convection in a saturated porous layer with a denser fluid on top of a lighter fluid has been extensively studied by means of a linear stability analysis, numerical simulations and the energy method ( (Bachu et al, 1994;Class et al, 2009;Dentz and Tartakovsky, 2009;Elder, 1968;Ennis-King et al, 2005;Foster, 1965;Gasda, 2010;Khosrokhavar et al, 2014c;Meulenbroek et al, 2013;Moortgat et al, 2009;Myint and Firoozabadi, 2013;Nordbotten and Celia, 2011;Nordbotten et al, 2005;Pruess et al, 2003;Ranganathan et al, 2012;Riaz et al, 2006;Van Duijn et al, 2004;Walker and Homsy, 1978)). …”
Section: Introductionmentioning
confidence: 99%
“…Molecular diffusion effect is important when we simulate gas injection processes in fractured media (Moortgat et al 2009; Yanze and Clemens 2012). Molecular diffusion has been ignored in many conventional reservoir simulation cases, but it can play a significant role in tight fractured reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…The capillary pressure contrast between the fracture and the matrix may also contribute to the low recovery efficiency in fractured reservoirs (Firoozabadi and Markeset, 1994). However, there is growing evidence that CO 2 injection can significantly improve oil recovery as a secondary or tertiary recovery mechanism in fractured reservoirs (Moortgat et al 2009). Laboratory experiments (Darvish et al 2006a, b;Darvish et al 2004;Øyno et al 1995) and simulation studies (Moortgat et al 2009;Alavian and Whitson, 2005;Darvish et al 2004) have demonstrated that CO 2 at elevated pressures can recover oil in fractured reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is growing evidence that CO 2 injection can significantly improve oil recovery as a secondary or tertiary recovery mechanism in fractured reservoirs (Moortgat et al 2009). Laboratory experiments (Darvish et al 2006a, b;Darvish et al 2004;Øyno et al 1995) and simulation studies (Moortgat et al 2009;Alavian and Whitson, 2005;Darvish et al 2004) have demonstrated that CO 2 at elevated pressures can recover oil in fractured reservoirs. In principle, the development of miscibility or near-miscibility may eliminate or reduce the capillary pressure contrast and enable the recovery of residual oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation